Comparison of three fixation methods in treatment of tibial fracture in adolescents. Issue 6 (21st November 2017) - Lin, Lixiang; Liu, Yang; Lin, Chuanlu; Zhou, Yifei; Feng, Yongzeng; Shui, Xiaolong; Yu, Kehe; Lu, Xiaolang; Hong, Jianjun; Yu, Yang
Abstract : Background: Tibial fractures are the most common musculoskeletal injury in adolescents. The optimal management of tibial fractures in adolescents is controversial. In this study, we compared the outcomes including complications of three fixation methods in tibial fractures of adolescents and explored the factors associated with the complications. Methods: A retrospective cohort study about 83 diaphyseal tibial fractures in 79 children and adolescents, who were treated with plate fixation (PF), elastic stable intramedullary nail fixation (ESINF), or external fixation (EF), was conducted. After adjustment for age, weight, energy of the injury, polytrauma, fracture level and pattern, and extent of comminution, treatment outcomes were compared in accordance with the length of the hospital stay, time to union, and complication rates including many factors. Results: The mean age of the patients was 13.4 years, and their mean weight was 44.2 kg. There was a loss of reduction in two of 33 fractures treated with ESINF and four of 13 treated with EF ( P < 0.001). At the time of final follow‐up, three patients (two treated with EF and one treated with ESINF) had ≥2.0 cm of shortening. Four of the 32 patients (33 fractures) treated with ESINF underwent a reoperation (two due to loss of reduction and one each because of delayed union and nonunion). Six patients treated with EF required a reoperation (four due to loss of reduction, one for malunion and one for replacement of a pin complicated by infection). Two fracture treated with PF required refixation attributing to nonunion and malunion. A multivariate analysis with adjustment for baseline differences showed that EF was associated with a 7.56‐times (95% confidence interval 3.74–29.87) greater risk of loss of reduction and/or malunion than ESINF. Conclusions: All three treatments had satisfactory outcomes, and EF was correlated with the highest rate of complications in our series of adolescents treated with a tibial fracture. However, we cannot currently recommend that all fractures might be suitable for ESINF. The choice of fixation will remain influenced by surgeon preference in term of expertise and experience, patient and fracture characteristics, and patients and family preferences.